2002
DOI: 10.1001/archotol.128.8.956
|View full text |Cite
|
Sign up to set email alerts
|

Head and Neck Muscle Spasm After Radiotherapy

Abstract: A subset of patients with irradiation-induced cervical muscle spasm benefit from treatment with botulinum toxin A injections. Further study is needed to more clearly define the entity and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Type-A botulinum toxin is an analgesic and a muscle relaxant and has been used to treat pain related to neck muscle spasm and contracture in post-XRT HNC patients. Along with conventional analgesics, future studies should explore Botulinum toxin injection and other therapies as therapeutic options to treat chronic pain in post-XRT HNC patients [37, 38].…”
Section: Discussionmentioning
confidence: 99%
“…Type-A botulinum toxin is an analgesic and a muscle relaxant and has been used to treat pain related to neck muscle spasm and contracture in post-XRT HNC patients. Along with conventional analgesics, future studies should explore Botulinum toxin injection and other therapies as therapeutic options to treat chronic pain in post-XRT HNC patients [37, 38].…”
Section: Discussionmentioning
confidence: 99%
“…Post-radiotherapy neck muscle spasm among HNC patients began to receive attention about two decades ago, however, to date, only three papers have been published regarding this adverse effect in HNC patients. Van Daele et al first reported the condition in 2002, finding that after RT in the neck area, 9 HNC patients suffered neck muscle spasm, concentrated in the SCM [ 9 ]. Then in 2011, Gelblum et al reported that 14 HNC patients developed severe neck spasm after undergoing IMRT ± chemotherapy [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated a strong dose-response relationship between neck muscle spasm and the radiation dose received by the SCM of HNC patients [ 9 ]. However, the independent prognostic variables for post-radiotherapy neck muscle spasm remain unclear; moreover, of the few published studies on the topic, none examined patients with NPC [ 8 – 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have shown focal loss of capillaries and muscle degeneration 2–4 months after a one-time 2000 rad (20 Gy) treatment. The damage increases collagen and decreases proteoglycans in extracellular matrix leading to disorganized structure and fibrotic tissue formation [ 11 ]. Focal pain is reported in about 20%–30% of patients after radiation therapy of head and neck cancer [ 12 , 19 ].…”
Section: Discussionmentioning
confidence: 99%